2012
DOI: 10.1007/s00021-012-0126-x
|View full text |Cite
|
Sign up to set email alerts
|

Blow-up of Solutions to the Generalized Inviscid Proudman–Johnson Equation

Abstract: For arbitrary values of a parameter λ ∈ R, finite-time blowup of solutions to the generalized, inviscid Proudman-Johnson equation is studied via a direct approach which involves the derivation of representation formulae for solutions to the problem. Mathematics Subject Classification (2010). 35B44, 35B10, 35B65, 35Q35.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(73 citation statements)
references
References 25 publications
2
71
0
Order By: Relevance
“…If we are solving this equation on S 1 , we should impose that S 1 ω = 0 (which we may assume on the initial data). Now we recall from [49] that this system satisfies…”
Section: First Examplementioning
confidence: 99%
“…If we are solving this equation on S 1 , we should impose that S 1 ω = 0 (which we may assume on the initial data). Now we recall from [49] that this system satisfies…”
Section: First Examplementioning
confidence: 99%
“…In the appendix, we also gave a physical derivation of the GPJ equation from the compressible, two-dimensional Euler equations. While the finite-time existence results in, e.g., [12,13] also specified the nature of the singularity, such as blow-up in the L p -norm of u x , Theorem 2.3 only guarantees that the solution cannot be extended, but does not give further information on the nature of the singularity. Does the solution blow up or does the solution lose its (Lipschitz) regularity, i.e., is there blow-up in its derivatives?…”
Section: Summary and Further Perspectivesmentioning
confidence: 99%
“…In [12], the authors showed, for a = 1, that there exist smooth initial data such that the solutions exist globally. Since their results were obtained with quite different techniques, it would be interesting to compare the singularity and global existences results in Theorem 2.3 for a ≥ 1 and a > −1 respectively to the case of a = 1 in [12] Also, it would be interesting to extend the flow map approach laid out in the present paper to also give information on how a solution becomes singular. This will, however, also require information on the second derivative of t → η(t), which has to be derived from new estimates.…”
Section: Summary and Further Perspectivesmentioning
confidence: 99%
“…Regularity criteria for non-smooth initial velocities, including piecewise-linear functions and maps with "cusps" and/or "kinks" on their graphs, can be studied via an argument similar to that used in the proof of Theorem 3.2 (see, e.g., [23,21]). …”
Section: Remark 34mentioning
confidence: 99%
“…(8) is known as the inviscid Proudman-Johnson equation [20]. In [23], a general solution formula for solutions of (8), along with blowup and global-in-time criteria, were established (see [3,4,24,19,21] for additional regularity results). Eq.…”
Section: Introductionmentioning
confidence: 99%